Effect of mixed rearing of barrows and gilts on backfat thickness and serum metabolite profiles of the Kagoshima‐Kurobuta (Berkshire) pig. (4th November 2021) - Ohkoda, Tsutomu; Yoshida, Katsunori; Ijiri, Daichi; Ohtsuka, Akira
Abstract: We investigated the effect of mixed rearing of barrows and gilts on the backfat thickness and the serum metabolite profiles of Kagoshima‐Kurobuta (Berkshire) pigs. A total of 149 pigs with an average body weight of 35 kg were divided into the following groups: 100%, 90%, 70%, 50%, 30%, 10%, and 0% groups consisting of 10 barrows (1 pen), 9 barrows + 1 gilt (3 pens), 7 barrows + 3 gilts (2 pens), 5 barrows + 5 gilts (3 pens), 3 barrows + 7 gilts (2 pens), 1 barrow + 9 gilts (3 pens), and 9 gilts (1 pen), respectively. All pigs were raised to a shipping weight of 120 kg. Mixed rearing significantly reduced ( p  < 0.001) backfat thickness, and the optimum mixing ratio of barrows and gilts was 7:3 (the 70% group). Four types of circulating sex steroids were found in both the barrows and gilts in the 50% group but were not detected in barrows from the 100% group. These results indicated that mixed rearing of barrows and gilts was effective for reducing the backfat thickness of barrows, and induced sex steroid hormones may influence the backfat thickness of barrows in mixed‐reared groups.